Can't pay, won't pay : the fight to stop the poll tax - Hannah, Simon (Pluto Press, 2020)
Thirty years ago, a social movement helped bring down one of the most powerful British Prime Ministers of the 20th Century. For the 30th anniversary of the Poll Tax rebellion, Simon Hannah looks back on those tumultuous days of resistance, telling the story of the people that beat the bailiffs, rioted for their rights and defied a government.